KEPENTINGAN INDONESIA BEKERJASAMA DENGAN BRAZIL DALAM BIDANG PERTAHANAN MILITER TAHUN 2010-2014 - Sihite, Hotmauli; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to explain the interests of Indonesia cooperate with Brazil in the field of military defense in 2010-2014. Brazil was chosen because it has excess in defense industry and plays an important role in the modernization of Indonesia’s defense equipment. The signed of MoU, has been done between the two countries since November 2010 which includes the purchased of Super Tucano EMB-314, Trasfer of Technology MLRS Astros II, the placement of the defense attache, and joint military exercises.The foreign policy decision-making models of Graham T.Allison consists of a rational actor model, organizational model, and bureaucratic model. This research used rational actor model. In this model, various actions of state analyzed under the assumption that a country considered all the options and act rationally to maximize profits. The government is regarded as the main actor who examines a set of goals, evaluate them based on the profit and then choose the one that gives an advantage.The result of this research show that when cooperate with Brazil, there are benefits for Indonesia, such as Indonesian defense equipment is getting better, education for soldiers, military equipment which are sophisticated, and placed the defense attache at the Embassy, JakartaKey words: foreign policy, military defense cooperation, modernization ofdefense equipment